1995
DOI: 10.1021/bi00006a002
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Hemagglutinin-Mediated Membrane Fusion: Influence of Receptor Binding on the Lag Phase Preceding Fusion

Abstract: Fusion of influenza virus with liposomes is triggered by low pH, resulting in a conformational change in the fusion protein (HA) and the insertion of fusion peptides from HA into the liposomal membrane. Fusion does not take place immediately after insertion but is preceded by a lag phase, the duration of which, as we have found previously, depends on the presence of ganglioside receptors in the liposomal membrane [Stegmann, T., White, J. M., & Helenius, A. (1990) EMBO J. 9, 4231-4241]. Here we have investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 32 publications
5
33
0
Order By: Relevance
“…Thus, the notion that the interaction between HA and a sialic-acid-containing receptor has a fundamental effect on the fusion process does not seem tenable. Rather, our present findings support previous conclusions of Stegmann et al [14,17] that gangliosides do not influence the low-pH-dependent conformational change of HA or the characteristics of the membrane merger itself.…”
Section: Streptavidin/biotin-mediated Ha-dependent Fusion"supporting
confidence: 90%
See 3 more Smart Citations
“…Thus, the notion that the interaction between HA and a sialic-acid-containing receptor has a fundamental effect on the fusion process does not seem tenable. Rather, our present findings support previous conclusions of Stegmann et al [14,17] that gangliosides do not influence the low-pH-dependent conformational change of HA or the characteristics of the membrane merger itself.…”
Section: Streptavidin/biotin-mediated Ha-dependent Fusion"supporting
confidence: 90%
“…These observations have implications for the mechanism of HA-mediated fusion. Sialic-acid-containing receptors, such as gangliosides, have been shown to enhance the rate [14,17] and extent [17] of influenza virus fusion in liposomal model systems, by increasing prefusion binding of the virus to the target membrane at neutral pH. In the absence of gangliosides, fusion is also observed, but the rates and extents are relatively low [14,17] (see also Fig.…”
Section: Streptavidin/biotin-mediated Ha-dependent Fusion"mentioning
confidence: 92%
See 2 more Smart Citations
“…From these observations, we concluded that HA-receptor binding that is too tight interferes with the enlargement of fusion pores. Many studies have been published concerning the relationship between HA binding and fusion activities (1,7,12,13,15,20,21,23), and most indicate that the binding of HA to receptors is necessary for an efficient fusion reaction. The question is whether this concept is inconsistent with our conclusions from the present study.…”
Section: Discussionmentioning
confidence: 99%